2020
DOI: 10.1021/acssensors.9b02314
|View full text |Cite
|
Sign up to set email alerts
|

Low-Cost Hydrogen Sensor in the ppm Range with Purely Optical Readout

Abstract: Due to the changing global climate, the role of renewable energy sources is of increasing importance. Hydrogen can play an important role as an energy carrier in the transition from fossil fuels. However, to ensure safe operations, a highly reliable and sensitive hydrogen sensor is required for leakage detection. We present a sensor design with purely optical readout that reliably operates between 50 and 100,000 ppm. The building block of the sensor is a reactive sample that consists of a layered structure wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 45 publications
0
32
0
Order By: Relevance
“…Another family of CN materials are those that combine layers of thin films and arrays of isolated nanodiscs. These materials, referred to as plasmonic perfect-absorberbased H 2 optical sensors [92][93][94][95], exploit changes in the reflectance during hydrogenation/dehydrogenation [92]. An example structure of such a material comprises of an array of Pd nanodiscs that is placed on top of a dielectric spacer (MgF 2 ) while the bottom layer is a metallic film (e.g., Au), which plays the role of a mirror (Figure 11a).…”
Section: Complex Nanostructured (Cn) Materials For Optical H 2 Sensorsmentioning
confidence: 99%
“…Another family of CN materials are those that combine layers of thin films and arrays of isolated nanodiscs. These materials, referred to as plasmonic perfect-absorberbased H 2 optical sensors [92][93][94][95], exploit changes in the reflectance during hydrogenation/dehydrogenation [92]. An example structure of such a material comprises of an array of Pd nanodiscs that is placed on top of a dielectric spacer (MgF 2 ) while the bottom layer is a metallic film (e.g., Au), which plays the role of a mirror (Figure 11a).…”
Section: Complex Nanostructured (Cn) Materials For Optical H 2 Sensorsmentioning
confidence: 99%
“…However, hydrogen gas is colorless, odorless, highly volatile, and flammable. Explosion is very easy to occur when hydrogen gas concentration exceeds 4% in dry air; therefore, safety has always been a big issue in hydrogen storage and use [5,6]. Developing a sensor for hydrogen gas is essential to monitor its amount for their applications in energy and environmental fields.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15] After Liu et al experimentally demonstrated a surface plasmon resonance (SPR) sensor with perfect absorption in the SPR structure, 16 many hydrogen sensors that use perfect absorption and SPR have been proposed. [17][18][19][20][21] Such optical hydrogen sensors with perfect absorption provide low insertion loss and high spectral contrast, which contribute to their high sensitivity and low detection limit. However, these sensors need bulky optical setups to ensure that the input and readout signals are properly coupled to optical detectors.…”
Section: Introductionmentioning
confidence: 99%